Effect of Y-trellis and vertical shoot positioning training systems on downy mildew and botrytis bunch rot of grape in highlands of southern Brazil - Bem B.P.D.* (2015)
© 2015 .Downy mildew (Plasmopara viticola) and botrytis bunch rot (Botrytis cinerea) are important diseases in the highlands of Santa Catarina State, a relatively new wine-growing region in Brazil. Although it is known that training systems can affect microclimate and subsequent disease development, this has not been examined in the highlands of Brazil. Thus, the purpose of this study was to evaluate the influence of Y-trellis (YT) and vertical shoot positioning (VSP) training system on downy mildew and botrytis bunch rot disease development in 'Cabernet Sauvignon' cultivar. Experiments were carried out in commercial vineyards in São Joaquim, SC Municipality, southern Brazil, during the year 2012-2013 and 2013-2014 growing seasons. Downy mildew incidence and severity were quantified weekly from the first symptoms appearance on leaves and botrytis bunch rot incidence was evaluated at harvest. Disease progress curves were constructed compared according to: (a) beginning of symptoms appearance; (b) time to maximum disease incidence and severity; (c) maximum disease incidence and severity; and (d) area under the incidence and severity disease progress curve. Results showed significant differences in downy mildew and botrytis bunch rot intensity among grape training systems, where VSP training system showed significantly lower area under the incidence and severity disease progress curve and intensity of downy mildew and botrytis bunch rot in both 2012-2013 and 2013-2014 growing seasons. Collectively, the results of this study suggest VSP training system should be recommended for grapevine production to reduce both downy mildew and botrytis bunch rot in the highlands regions of southern Brazil.